2017
DOI: 10.1097/bot.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Review of Helical Blade Versus Lag Screw Fixation for Cephalomedullary Nailing of Low-Energy Peritrochanteric Femur Fractures: There is a Difference in Cutout

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 20 publications
6
46
1
Order By: Relevance
“…We observed axial migration of the helical blade although the blade shaft was allowed to slide freely in the test fixture. Clinical series of intertrochanteric fractures demonstrated similar failure mechanisms as observed in our study . Deficient lateral buttress and unstable calcar patterns as mimicked by our test setup, have been described as additional factors for nail toggling and medial migration in intertrochanteric fractures …”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…We observed axial migration of the helical blade although the blade shaft was allowed to slide freely in the test fixture. Clinical series of intertrochanteric fractures demonstrated similar failure mechanisms as observed in our study . Deficient lateral buttress and unstable calcar patterns as mimicked by our test setup, have been described as additional factors for nail toggling and medial migration in intertrochanteric fractures …”
Section: Discussionsupporting
confidence: 83%
“…Helical blades exhibited axial migration with joint perforation in clinical series and revealed a higher cutout rate compared to other implant designs. 12,[24][25][26] A previous biomechanical study reported different direction of the migration vector of helical blades in comparison to dynamic hip screws. 4 We observed a nearly equidistant cranial/vertical and axial migration of helical blades in our test setup.…”
Section: Tip-apex Distance Of Helical Bladesmentioning
confidence: 99%
See 3 more Smart Citations